Penilaian Kinerja Operasi dan Pemeliharaan Bendungan Keuliling dengan Pendekatan Indeks Kondisi - Marini Bravikawati; Amalia Harmin (Fakultas Teknik Universitas Cenderawasih, 2024)
The Keuliling Dam has an important role in meeting water supply needs in the surrounding area. After operating for more than 10 years, an evaluation of operation and maintenance performance is required to ensure its continued function. This research aims to analyze the condition of the Keuliling Dam through assessing the condition index for each dam component based on primary and secondary data. The assessment is carried out by providing a condition index value that reflects the level of damage to the safety aspects and environmental performance of the dam. The results of the analysis show that the condition index value for the Keuliling Dam is 4, which is included in the minor damage category. This condition indicates the need for maintenance action to prevent further damage. Based on observations, deposition of material and rubbish is one of the main problems that affects dam performance. This research provides an important basis for managers in determining strategic steps to improve the performance of dam operations and maintenance. The evaluation carried out aims to ensure that the Keuliling Dam can continue to function optimally, support water supply, and minimize the risk of more serious damage. It is hoped that the recommendations from this research can become a reference in managing dams effectively and efficiently.